A research annual - Biddle, Jeff; Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2003)
This volume contains edited articles on works by Adam Smith, John Maurice Clark, John Maynard Keynes, Knight and Copeland and Sergius Bulgakov. It also features review essays on books covering evolutionary theory, methodology, and economic philosophy and ideology.